Financial Viability of Electricity Sectors in Sub-Saharan Africa : Quasi-Fiscal Deficits and Hidden Costs - Trimble, Chris (World Bank, Washington, DC, 2016)
This paper studies the financial viability of electricity sectors in 39 countries in Sub-Saharan Africa using an approach similar to that in an earlier study, the Africa Infrastructure Country Diagnostic. The quasi-fiscal deficit in each country is calculated under two scenarios: existing utility performance and benchmark utility performance. In the first scenario, only two countries have a financially viable electricity sector (the Seychelles and Uganda). Only 19 countries cover operating expenditures, while several countries lose in excess of US$0.25 per kilowatt-hour sold. Quasi-fiscal deficits average 1.5 percent of gross domestic product, and exceed 5 percent of gross domestic product in several countries. In this context, it will be difficult for utilities to maintain existing assets let alone facilitate the expansion needed to reach universal access goals. The number of countries with a quasi-fiscal deficit below zero increases to 13 under the second scenario, and to 21 when oil price impacts are considered, indicating tariff increases may not be needed at benchmark performance in these cases. Combined network and collection losses on average represent a larger hidden cost and are less politically sensitive to address than underpricing, so could be a smart area for policy focus to reduce quasi-fiscal deficits. Underpricing remains an issue to address over the medium term, as service quality improves. With no changes in power mix, tariffs would need to increase by a median value of US$0.04 per kilowatt-hour sold at benchmark performance, representing a 24 percent increase on existing tariffs. Most countries have improved or maintained performance, and relatively few countries have had declining financial viability.